2018
DOI: 10.1002/clc.22908
|View full text |Cite
|
Sign up to set email alerts
|

The short‐ and long‐term outcomes of percutaneous intervention with drug‐eluting stent vs bare‐metal stent in saphenous vein graft disease: An updated meta‐analysis of all randomized clinical trials

Abstract: The use of drug-eluting stents (DES) vs bare-metal stents (BMS) in saphenous vein graft (SVG) lesions remains controversial. We conducted a meta-analysis of all randomized clinical trials comparing the outcomes of DES with BMS in SVG percutaneous coronary interventions. A search of PubMed, Embase, the Cochrane Register of Controlled Trials, and Clinicaltrials.gov was performed for all randomized clinical trials. We evaluated the short- and long-term clinical outcomes of the following: all-cause mortality, majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…During long-term follow-up, the 2 larger studies showed no difference between DES and BMS (54,56), and another showed worse outcomes with DES (59). In a meta-analysis of the 6 previously mentioned randomized trials by Kheiri et al (60), there were no significant differences between DES and BMS in the long-term incidence of MACE, target lesion revascularization, target vessel revascularization, stent thrombosis, and all-cause mortality. 1 and 2.…”
Section: Stent Selection In Svg Pcimentioning
confidence: 85%
“…During long-term follow-up, the 2 larger studies showed no difference between DES and BMS (54,56), and another showed worse outcomes with DES (59). In a meta-analysis of the 6 previously mentioned randomized trials by Kheiri et al (60), there were no significant differences between DES and BMS in the long-term incidence of MACE, target lesion revascularization, target vessel revascularization, stent thrombosis, and all-cause mortality. 1 and 2.…”
Section: Stent Selection In Svg Pcimentioning
confidence: 85%
“…Regarding the choice of the stent, recent studies suggest that drug‐eluting stents may offer an advantage over bare‐metal stents. Long‐term results are better with PCI than with medical treatment alone but are far from ideal and are indeed worse than outcomes of patients without vein graft failure 7,69 …”
Section: Resultsmentioning
confidence: 99%
“…According to our case, the patient received drug-eluting stent (DES) for SVG PCI. Previous studies comparing DES and bare-metal stent (BMS) in the SVG intervention found that DES was superior over BMS in terms of reducing short-term MACE, total lesion revascularization (TLR), and TVR significantly [13 , 16] . Additionally, to improve the outcomes of revascularization, dual-antiplatelet therapy using aspirin and ticagrelor is indicated significantly increased graft patency after 1 year vs aspirin alone [17] .…”
Section: Discussionmentioning
confidence: 99%